ALGEBRAIC ON MAGIC SQUARE OF ODD ORDER n - Mahyuddin . (Proceedings of ICMSA, 2005)
In this paper we described the relation betrreen a magic square of oddorder n and a group, and their properties. By the modulo number n, weconstruct entries for each table from initial table of magic square withlarge number n2. Generalization of the underlying ideas are presented, we have unique group, and we also prove variants of the main result formagic cubes.Keywords: entry, anay, algorithm, magic cubes, group.